1973
DOI: 10.1029/jb078i035p08429
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the physical parameters of 5759 faint radio meteors

Abstract: The results of an analysis of about 6000 meteors detected in 1962 from at least three different stations located around Havana, Illinois, under the Harvard Radio Meteor Project are presented. Each station yields instantaneous values of the meteor velocity υ and the electron line density q in the trail, thus permitting the determination of the mean deceleration and a sketch of the ionization curve. From the ionization curve we can compute the meteor mass m∞. It is then possible with the aid of some assumptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 19 publications
5
61
0
Order By: Relevance
“…We summarise the conclusions from Greenberg and Hage (1990), which were based on a broader discussion: a high coma dust porosity of 0.93 < P < 0.975 is a likely possibility which is consistent with (a) the direct results of this work, (b) comet densities as deduced independently by other workers (Sagdeev et al 1988, Sekanina andYeomans 1985) and (c) observed meteor densities (Verniani 1973). Furthermore, there are two additioanl features in the present model of comets which are critical'm producing the observed 9.7 fim and 3.4 \xm coma dust emissions: (1) The presence of organic refractory material.…”
Section: Resultssupporting
confidence: 78%
“…We summarise the conclusions from Greenberg and Hage (1990), which were based on a broader discussion: a high coma dust porosity of 0.93 < P < 0.975 is a likely possibility which is consistent with (a) the direct results of this work, (b) comet densities as deduced independently by other workers (Sagdeev et al 1988, Sekanina andYeomans 1985) and (c) observed meteor densities (Verniani 1973). Furthermore, there are two additioanl features in the present model of comets which are critical'm producing the observed 9.7 fim and 3.4 \xm coma dust emissions: (1) The presence of organic refractory material.…”
Section: Resultssupporting
confidence: 78%
“…Masses are computed by calculating the electron-line density q of the echo based on its received power, location in the radar beam and range. The mass-velocity-ionization relation of Verniani (1973) is then used to convert from q to m. Particles smaller than ∼200 μm were not detected in the NT source because their typical impact speeds make the ionization factor I smaller than I . Indeed, we observe a strong D versus V correlation whose low-end closely follows the I I 1 limit.…”
Section: Observationsmentioning
confidence: 99%
“…To relate the meteor overdense duration, T , to the mass of a meteoroid we have used the formula for maximum electron line density, α max , as a function of the meteoroid mass, M ∞ , its velocity, V, and radiant position embodied by the zenith distance, z r , which had been published by Verniani (1973) α max = 2.73 × 10 10 M 0.92…”
Section: Mass Distributionmentioning
confidence: 99%